Misunderstanding Metaethics: Difficulties Measuring Folk Objectivism and Relativism (Diametros, 2020)
Recent research on the metaethical beliefs of ordinary people appears to show that they are metaethical pluralists that adopt different metaethical standards for different moral judgments. Yet the methods used to evaluate folk metaethical belief rely on the assumption that participants interpret what they are asked in metaethical terms. We argue that most participants do not interpret questions designed to elicit metaethical beliefs in metaethical terms, or at least not in the way researchers intend. As a result, existing methods are not reliable measures of metaethical belief. We end by discussing the implications of our account for the philosophical and practical implications of research on the psychology of metaethics.